2016
DOI: 10.1080/13102818.2016.1240593
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review of anti-hepatitis B virus activity of medicinal plants

Abstract: Medicinal plants are of undoubted value, as they have been used for centuries to treat various diseases and health disorders in almost every part of the world. In several studies, the use of medicinal plants was found effective in treatment of infectious and non-infectious diseases. The World Health Organization has been working for many years to identify all surviving medicinal plants on the earth. An important step has also been taken by the Natural Health Product Regulation of Canada for promotion and usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…It is a medicinal plant popularly known as stonebreaker, as it has historically been used in the elimination of kidney stones, commonly used as an herbal medicine [ 3 ]. Its clinical effects include antihepatotoxic, antilytic, antihypertensive, anti-inflamatory, anti-human immunodeficiency virus (HIV), and anti-hepatitis B activities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a medicinal plant popularly known as stonebreaker, as it has historically been used in the elimination of kidney stones, commonly used as an herbal medicine [ 3 ]. Its clinical effects include antihepatotoxic, antilytic, antihypertensive, anti-inflamatory, anti-human immunodeficiency virus (HIV), and anti-hepatitis B activities [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that various compounds isolated from these plants display promising bioactivity. 16 A number of medicinal plants from various countries have been tested for anti-HBV to find potential candidates for anti-HBV drug development. The goal of HBV therapy is to prevent the progression of chronic hepatitis B to cirrhosis, end-stage liver disease, hepatocellular carcinoma and death.…”
Section: Discussionmentioning
confidence: 99%
“…Nishikori et al 93 95 Elsebai et al 96 concluded that grosheimol and cynaropicrin of wild Egyptian artichoke (Cynara cardunculus L.) are promising candidates for the development of new pan-genotypic entry inhibitors of HCV infection. Siddiqui et al 97 reported that the drugs available on the market for the treatment of hepatitis B are not sufficient and also cause side effects in patients suffering from HBV infection. Wan et al 98 reported that extract of Cananga odorata could be a good candidate for the development of anti-HBV drugs.…”
Section: Reishi Mushroom (Ganoderma Lucidum)mentioning
confidence: 99%